An estimated stochastic dynamic general equilibrium model of the euro area - Frank Smets; Raf Wouters (European Central Bank (ECB), 2002)
This paper develops and estimates a stochastic dynamic general equilibrium (SDGE) model with sticky prices and wages for the euro area. The model incorporates various other features such as habit formation, costs of adjustment in capital accumulation and variable capacity utilisation. It is estimated with Bayesian techniques using seven key macro-economic variables: GDP, consumption, investment, prices, real wages, employment and the nominal interest rate. The introduction of ten orthogonal structural shocks (including productivity, labour supply, investment, preference, cost-push and monetary policy shocks) allows for an empirical investigation of the effects of such shocks and of their contribution to business cycle fluctuations in the euro area. Using the estimated model, the paper also analyses the output (real interest rate) gap, defined as the difference between the actual and model-based potential output (real interest rate).
Keywords: E4; E5; 330; euro area; monetary policy; SDGE models